Comparison of Apoptotic Inducing Effect of Zerumbone and Zerumbone-Loaded Nanostructured Lipid Carrier on Human Mammary Adenocarcinoma MDA-MB-231 Cell Line. (18th November 2014) - Hosseinpour, Mahnaz; Abdul, Ahmad Bustamam; Rahman, Heshu Sulaiman; Rasedee, Abdullah; Yeap, Swee Keong; Ahmadi, Negin; Othman, Hemn Hassan; Chartrand, Max Stanley
Abstract : This study investigated the anticancer effect of zerumbone (ZER) and zerumbone-loaded nanostructured lipid carrier (ZER-NLC) on the human mammary gland adenocarcinoma (MDA-MB-231) cell line. The effect of ZER and ZER-NLC on MDA-MB-231 cells was determined via electron and fluorescent microscopy and flow cytometry using the Annexin V, cell cycle, and Tdt-mediated dUTP nick-end labeling assays. We demonstrated that ZER and ZER-NLC significantly suppressed the proliferation of MDA-MB-231 cells with an IC50 of 5.96 ± 0.13 and 6.01 ± 0.11  μ g/mL, respectively. ZER and ZER-NLC arrested MDA-MB-231 cell cycle at the G2/M phase. The induction of apoptosis by ZER and ZER-NLC was via the intrinsic pathway through the release of cytochrome c and activation of caspase-3 and caspase-9. The treatments also caused the downregulation of antiapoptotic Bcl-2, Bcl-xL proteins, and proliferating cell nuclear protein and upregulation of proapoptotic Bax protein. Therefore, loading of ZER into NLC did not compromise the anticancer effects of ZER on MDA-MB-231 cells. In conclusion, ZER-NLC, which increased the bioavailability of ZER, is an effective agent in the treatment of cancers.